2007
DOI: 10.1007/s10198-007-0075-0
|View full text |Cite
|
Sign up to set email alerts
|

Preferences and utilities for the symptoms of moderate to severe allergic asthma

Abstract: The range of utility values (0.71-0.78) demonstrates the severity of moderate to severe allergic asthma. However the spread of scores between complete control of asthma and worsening of asthma was lower than was expected. The community sample placed only a moderate value on the avoidance of all asthma symptoms in the DCE survey. The results suggest that the community sample may not have fully understood the benefits of control over asthma symptoms and the limitations such symptoms can impose on everyday life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
(18 reference statements)
0
12
0
3
Order By: Relevance
“…While respondents placed the most value on avoidance of daytime symptoms, they also reported a higher WTP to avoid waking up in the night, and not requiring an inhaler compared to waking up with symptoms and requiring an inhaler. The authors acknowledged that this may not be intuitively correct, and postulated that the result may have been due to the respondents’ not fully understanding the nature of inhaler use and its link with the severity of symptoms 43. McTaggart-Cowan et al reported that patients with asthma preferred a treatment regimen that resulted in more symptom-free days but were willing to forego some of this benefit in exchange for a more convenient regimen or a reduction in the frequency of adverse events 44…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While respondents placed the most value on avoidance of daytime symptoms, they also reported a higher WTP to avoid waking up in the night, and not requiring an inhaler compared to waking up with symptoms and requiring an inhaler. The authors acknowledged that this may not be intuitively correct, and postulated that the result may have been due to the respondents’ not fully understanding the nature of inhaler use and its link with the severity of symptoms 43. McTaggart-Cowan et al reported that patients with asthma preferred a treatment regimen that resulted in more symptom-free days but were willing to forego some of this benefit in exchange for a more convenient regimen or a reduction in the frequency of adverse events 44…”
Section: Resultsmentioning
confidence: 99%
“…However, each study had limitations that may affect the rigor of the results. In the Lloyd et al43 study, it was unclear whether the sample size was sufficient to capture reliable estimates. Furthermore, a high proportion of participants failed the consistency check in the survey, rendering the sample even smaller.…”
Section: Discussionmentioning
confidence: 99%
“…VAS ratings show a much larger difference between the best and worst health state. 72 The authors suggest that VAS data should not be used to inform cost-effectiveness analyses. 72 The SG data should be considered the primary source of utility data.…”
Section: Lloyd Et Al Observed That Standard Gamble (Sg) and Visual Anmentioning
confidence: 98%
“…72 The authors suggest that VAS data should not be used to inform cost-effectiveness analyses. 72 The SG data should be considered the primary source of utility data. 72 Szende and colleagues observed that when the EQ-5D was used to derive values for asthma health states, a high proportion of patients reported a value of '1'.…”
Section: Lloyd Et Al Observed That Standard Gamble (Sg) and Visual Anmentioning
confidence: 98%
See 1 more Smart Citation